Contemporary communication systems - Mesiya, Mohammed Farooque (McGraw-Hill/Irwin, 2013)
Provides a comprehensive introduction to analog and digital communication systems. This book explores the impact of semiconductor revolution (Moore's law) and software technologies in the realization of modern digital communication systems.